Gambaran Tingkat Kepuasan Mutu Pelayanan Poliklinik Gigi Rumah Sakit TK. IV Samarinda Selama Masa Pandemi COVID-19: The Description of Satisfaction Level towards Quality Service at Dental Polyclinic of Hospital TK. IV Samarinda during the COVID-19 Pandemic - Dea Pratiwi Sadaningsih; Listiyawati Listiyawati; Imran Irsal (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Dental care has been significantly impacted by the COVID-19 pandemic. Aerosol dispersal in most dental procedures can present a high risk of infection to both dentists and patients. Dental Polyclinic of Tk.IV Hospital is one of the hospitals in Samarinda that is still operating during the pandemic COVID-19, implementing health protocols such as limiting dental procedures and reducing dental visits. These restrictions will probably affect patients’ perceptions of service quality they receive and show health quality service provided by the hospital. This study aims to describe the level of satisfaction towards service quality at the Dental Polyclinic of Tk.IV Hospital Samarinda during the COVID-19 pandemic. This descriptive observational study was based on interview and questionnaire administration for 104 patients with inclusion and exclusion criteria. Two variables observed in this study were service quality with SERVQUAL dimension and patients’ level of satisfaction. The findings revealed that the average patients’ level of satisfaction was 92.62%. The dimensions of tangible 91.4%, reliability 92.8%, responsiveness 92.55%, assurance 93.93%, and empathy 92.45% were satisfactory, ranging from 81% and 100%. In general, according to those five dimensions, patients reported that the service quality was excellent and very satisfactory